2020
DOI: 10.1073/pnas.1917132117
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of critically endangered Nassau grouper ( Epinephelus striatus ) in the Cayman Islands following targeted conservation actions

Abstract: Many large-bodied marine fishes that form spawning aggregations, such as the Nassau grouper (Epinephelus striatus), have suffered regional overfishing due to exploitation during spawning. In response, marine resource managers in many locations have established marine protected areas or seasonal closures to recover these overfished stocks. The challenge in assessing management effectiveness lies largely in the development of accurate estimates to track stock size through time. For the past 15 y, the Cayman Isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 57 publications
0
51
0
Order By: Relevance
“…Round-trip migration distances covered by Nassau grouper in The Bahamas can exceed 300 km , thus surpassing distances reported for fish in the Cayman Islands and Belize (e.g., Whaylen et al, 2004;Semmens et al, 2007;Starr et al, 2007). The migratory patterns displayed by Nassau grouper in this study are congruent with previous research in The Bahamas in terms of routes and distances 1 https://www.seatemperature.org/central-america/bahamas/nassau.htm (∼15.7-176 km) traveled (Bolden, 2000;Stump et al, 2017).…”
Section: Tagging and Telemetrymentioning
confidence: 82%
“…Round-trip migration distances covered by Nassau grouper in The Bahamas can exceed 300 km , thus surpassing distances reported for fish in the Cayman Islands and Belize (e.g., Whaylen et al, 2004;Semmens et al, 2007;Starr et al, 2007). The migratory patterns displayed by Nassau grouper in this study are congruent with previous research in The Bahamas in terms of routes and distances 1 https://www.seatemperature.org/central-america/bahamas/nassau.htm (∼15.7-176 km) traveled (Bolden, 2000;Stump et al, 2017).…”
Section: Tagging and Telemetrymentioning
confidence: 82%
“…Other aggregating groupers are also threatened, including goliath grouper, Epinephelus itajara, and gag grouper, Mycteroperca microlepis (Coleman et al, 1996;Koenig et al, 2018;Bertoncini et al, 2018), at least partly due to fishing on their aggregations (Sadovy de Mitcheson and Colin, 2012). On the other hand, examples of recovery following successful protection, while few, are growing (Nemeth, 2005;Hamilton et al, 2011;Waterhouse et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term monitoring at locations where fishing communities have effectively removed or reduced fishing pressure on FSAs has shown that depleted FSAs can recover populations restoring ecosystem integrity and the flow of ecosystem goods and services (Aburto-Oropeza et al 2011;Chollett et al 2020;Hamilton et al, 2011;Kobara et al, 2013;Nemeth, 2005) (Figure 1). For example, a fisher-scientist-manager partnership in the Cayman Islands monitoring FSAs for 15 years found that Nassau grouper populations had tripled in response to conservation efforts (Waterhouse et al, 2020). In the U.S. Caribbean, average density and biomass of spawning red hind (E. guttatus) increased by over 60% within 5years of a permanent fishery closure (44 km 2 ) implemented through a partnership between fishers, local scientists and fishery managers (Nemeth, 2005).…”
Section: Fish Spawning Aggregations As Sentinels Of Ecological Changementioning
confidence: 99%